Pharmacokinetics and pharmacodynamic effects in koi carp (Cyprinus carpio) following immersion in propofol. (July 2018) - Oda, Ayako; Messenger, Kristen M.; Carbajal, Liliana; Posner, Lysa P.; Gardner, Brett R.; Hammer, Scott H.; Cerreta, Anthony J.; Lewbart, Gregory A.; Bailey, Kate M.
Abstract: Objective: To test the hypothesis that plasma propofol concentration (PPC) is associated with anesthetic effect in koi carp administered propofol by immersion. Study design: Prospective study. Animals: Twenty mature koi carp (mean ± standard deviation, 409.4 ± 83.7 g). Methods: Fish were immersed in propofol (5 mg L –1 ). Physiological variables and induction and recovery times were recorded. In phase I, blood was sampled for PPC immediately following induction and at recovery. In phase II, following induction, fish were maintained with propofol (4 mg L –1 ) via a recirculating system for 20 minutes. Following established induction, blood was sampled at 1, 10 and 20 minutes. In phase III ( n  = 19), fish were anesthetized as in phase II with blood sampled nine times in a sparse sampling strategy. Simultaneously, a pharmacodynamics rubric was used to evaluate anesthetic depth. PPC was determined using high performance liquid chromatography with fluorescence detection. Following evaluation of normality, data were analyzed using paired t test or Spearman correlation test (significance was set at p < 0.05). Results: In phase I, mean PPCs at induction (20.12 μg mL –1 ) and recovery (11.62 μg mL –1 ) were different ( p < 0.001). In phase II, only mean PPCs at induction (17.92 μg mL –1 ) and 10 minutes (21.50 μg mL –1 ) were different ( p  = 0.013). In phase III, a correlation between PPCs and the pharmacodynamic rubric scores was found ( p < 0.001, r  = –0.93). There was no correlation between PPCs and recovery time ( p  = 0.057, r  = 0.433). A two-compartment open model was chosen for the pharmacokinetic model. Absorption rate constant, elimination rate constant and intercompartmental rate constant were 0.48, 0.006 and 0.02 minute –1, respectively. Conclusions and clinical relevance: Measurable PPCs were achieved in koi carp anesthetized with propofol by immersion. Anesthetic depth of fish was negatively correlated with PPCs, but recovery time was not.